Evaluating Economic and Environmental Impact of A Plastic Waste Processing Industry nased on Circular Economy using Benefit-Cost Analysis - Asep Ridwan; Triwin R. Ambarwaty; Nuraida Wahyuni; Dyah L. Trenggonowati; Achmad Bahauddin; Ani Umyati; Bobby Kurniawan (Jurnal Ilmiah Teknik Industri, 2022)
Plastic has played a dominant role in human life as its usage is increasing over time. Plastic waste can harm the environment because plastic is not biodegradable. A collaboration adopted from the quintuple helix model was initiated by the local government of Cilegon, Indonesia, industry, and community to tackle the plastic waste problem. Plastic waste from households and industry is collected and processed in the plastic waste processing industry using the pyrolysis method producing gasoline, diesel, and kerosene. Kerosene is used by the community as fuel for cooking, whereas diesel and gasoline are used as boat fuels by fishermen. The collaboration is expected to provide economic and environmental benefits for the people in the Cilegon area. We conducted a cost and benefit analysis to evaluate the feasibility of this project from an economic and ecological point of view. The results will be used as input for conducting similar projects in other cities.